Secure And Energy Efficient Stochastic Optimized Routing Protocol for Mobile Ad Hoc Network - Bhavsar, Krunal Sudhirbhai (Asian Journal of Electrical Sciences, 2020)
Mobile Ad-hoc Network is a wireless mobile nodes network, which forms a network without any pre existing fixed network infrastructure support. MANET permits versatile communication between hosts that are moving around. MANETs have numerous advantages compared to traditional wireless networks. In MANET, each mobile node needs the cooperation of other nodes in the network for forwarding data packets from source to destination node. Mobile Ad-hoc Network includes different routing protocols for communication and in MANET each mobile node can act as host as well as sender or receiver at the same time. MANET is design to smartly react to network changes and operates without human interference to support nodes mobility. Mobile Ad-hoc Networks are designed to sustain its survivability in unfriendly and hostile conditions such as natural disasters and other emergency conditions. However unique characteristics of MANETs topology such as open peer-to-peer architecture, dynamic network topology, shared wireless medium and limited resource (battery, memory and computation power) pose a number of non-trivial challenges to security design. These challenges and characteristics require MANETs to provide broad protection and desirable network performance. Due to dynamic nature of MANET it is very challenging work to employ a secure route. The routing protocols play important role in transferring data. Mobile Ad Hoc Networks (MANETs) pose challenges in terms of energy control, due to their fixed transmission power, the mobility of nodes and a constantly changing topology. High levels of energy are needed in wireless networks, particularly for routing. In order to address this problem, energy enhancement is analyzed with the proposed dynamic AODV cluster base trust protocol, with the aim of maximizing the lifetime of the network. We have performed simulation of our approach to justify our research work on network simulator-2 (NS-2). Simulation result presents that our proposed approach result is improved the performance of network than the existing Mobile Ad hoc Network protocol.